Cerebral Vasospasm and Hemodynamic Alterations Following Aneurysmal Subarachnoid Hemorrhage Revealed with Combined CT Perfusion and CT Angiography - Zhao, Yiping; Zhang, Bo; Zhang, He; Xu, Ke; Li, Songbai (Journal of Neurology and Epidemiology, 2014)
Purpose: Vasospasm following aneurysmal subarachnoid hemorrhage (SAH) is considered to be one of the major factors leading to neurological deficits and is associated with poor outcome in SAH. In this study, we utilized combined computed tomography angiography (CTA) and CT perfusion (CTP) techniques to assess radiographic cerebral vasospasm with attempts (1) to determine if cerebral vasospasms can be detected in patients with onset of SAH less than 3 days, and (2) to assess the perfusion deficits or hemodynamic alterations of the affected brain tissues following acute or delayed SAH. Materials and Methods: Thirty-eight patients with SAH and seven without SAH were recruited in the present study. After SAH was confirmed with a baseline non-enhanced head CT scan, the combined CTA-CTP procedures were performed and the CTP maps were created simultaneously. Quantitative CTP measurements including cerebral blood volume (CBV), cerebral blood flow (CBF), mean transit time (MTT) and time-to-peak (TTP) were carried out for each of the territories in the anterior cerebral artery (ACA), the middle cerebral artery (MCA) and the posterior cerebral artery (PCA), respectively. Results: Among 38 patients with SAH, a total of 33 aneurysms were detected and their anatomic locations were as follows: PCA (17), ACA (10) and MCA (6), respectively. Furthermore, multiple aneurysms were also present in 7 of the 33 patients with SAH. Whole-brain CTP measurements showed perfusion deficits in all of the patients with SAH. Both CBV and CBF values were significantly reduced in the affected areas of brain tissues. The incidence of cerebral vasospasm was significantly higher in the patients with delayed SAH (61.5%) than those with onset of SAH in less than 3 days (12%) (Fisher exact test, p<0.05). Additionally, quantitative analysis of CTP measurements of the patient without cerebral vasospasms with those with CVS reveals that, when compared to the control, all the patients with or without cerebral vasospasms showed significant differences in all four parameters measured (p<0.05, one-way ANOVA). Furthermore, according to their corresponding territories of the ACA, MCA and PCA, there were significant decreases in the mean CBV and CBF values of the ACA, MCA and PCA of SAH patients compared to the control patients, respectively. Moreover, a significant prolongation in the mean MTT and TTP values in SAH patients was also evident. Conclusion: Although a much higher incidence of cerebral vasospasms usually occurs in the delayed SAH, cerebral vasospasm could be detected in less than three days following the onset of acute SAH. Furthermore, the combined CTA-CTP procedures, along with the baseline CT scan, could also offer diagnostic benefits for assessing changes in global perfusion following the onset of aneurysmal SAH.